PEMANFAATAN ALGORITMA C4.5 UNTUK MENENTUKAN BONUS TAHUNAN - Johan, Faul; Arnomo, Sasa Ani (Universitas Putera Batam, 2020)
Umano Vero Store is one of the stores that sells sales of bags, shoes, sandals, belts and wallets located in Batam, Indonesia. In the year 2019, known in the store Umano vero in determining the annual bonus to employees still not even evenly, employees at the store Umano Vero not satisfied with the annual bonus they received so that this problem raises less employee performance, employee discipline, and employee loyalty to the store Umano Vero.So the author performs analysis in the utilization of algorithm C4.5 to determine the annual bonus on the store Umano Vero. In the implementation of research, the authors perform methods or techniques of data mining using decision tree Classification or decree tree as well as algorithm type C4.5 done by manually calculation and also use Weka application version 3.9.2. Results of calculations and tests, the author also argues that from the process of utilization of algorithm C4.5 in determining the annual bonus that is done turns out to be sufficiently large influenced by some attributes of the annual bonus variable, namely the target attribute, the presence attribute and the work period attributes.